A Looking-Glass of Non-Coding RNAs in Oral Cancer - Alexandra Iulia Irimie (International Journal of Molecular Sciences, 2017)
Oral cancer is a multifactorial pathology and is characterized by the lack of efficient treatment and accurate diagnostic tools. This is mainly due the late diagnosis; therefore, reliable biomarkers for the timely detection of the disease and patient stratification are required. Non-coding RNAs (ncRNAs) are key elements in the physiological and pathological processes of various cancers, which is also reflected in oral cancer development and progression. A better understanding of their role could give a more thorough perspective on the future treatment options for this cancer type. This review offers a glimpse into the ncRNA involvement in oral cancer, which can help the medical community tap into the world of ncRNAs and lay the ground for more powerful diagnostic, prognostic and treatment tools for oral cancer that will ultimately help build a brighter future for these patients.